PENGARUH CITRA SEKOLAH, KUALITAS PELAYANAN, DAN KINERJA GURU TERHADAP KEPUASAN SISWA DI SMK NEGERI 4 HALMAHERA UTARA - Baeruma, Verowati Nona; Karnawati, Tin Agustina; Murtianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of school image, service quality, and teacher performance on student satisfaction at SMK Negeri 4 Halmahera Utara. Student satisfaction is a key indicator in assessing the success of educational services in schools. This research employs a quantitative approach with data collected through questionnaires distributed to students. The respondents consist of 93 students from grades X, XI, and XII, selected using a saturated sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that school image, service quality, and teacher performance simultaneously have a significant effect on student satisfaction. Partially, each of these variables also shows a positive and significant influence. These findings confirm that the better the school image, the quality of service, and the performance of teachers, the higher the level of student satisfaction. This serves as an important input for schools in their efforts to improve the overall quality of educational services.